A geografia das redes de serviços de saúde no Cariri cearense - Fernandes, Jefferson Santos (2020)
The organization of the Unified Health System is based on three pillars: network (integration of services), regionalization (agreement between municipalities) and hierarchization (levels of complexity of care). In this context, the present work aims to analyze the regional policy of the SUS in Cariri Ceará, highlighting the centrality of the urban cluster Crajubar - acronym resulting from the junction of the cities of Crato, Juazeiro do Norte and Barbalha. To achieve this work, we conducted bibliographic research on urban network, region and regionalization of health, analysis of the Master Plan for Health Regionalization of Ceará and the studies of the Brazilian Institute of Geography and Statistics on the Regions of Influence of Cities, as well as the survey data in the Department of Informatics of SUS. We found that the overlaps and imbalance of the urban network can manifest in several ways, and one of them is that of the health care and surveillance system. The cities of Crato, Juazeiro do Norte and Barbalha are consolidated as a pole of an expressive urban network in the central hinteries of the Brazilian Northeast. However, the analysis of the supply medical equipment and services and the socioeconomic conditions of the population of 45 municipalities in the Cariri Macroregion, revealed the need to strengthen local health networks and forms of social protection for the economically more vulnerable population. With the crisis caused by pandemic of the new Coronavirus, the weaknesses of the regional health system have been exacerbated, and there is therefore a large space for the intervention of public managers.